Enterocolic Fistula: A Rare Presentation of Cytomegalovirus Infection - Richdeep S Gill; Geoffrey Taylor; Robert M Penner; Sarvesh Logsetty (Canadian Journal of Infectious Diseases and Medical Microbiology)
In the present report, the first reported case of cytomegalovirus (CMV)-associated enterocolic fistula in an HIV/AIDS patient is described. CMV colitis is the second most common presentation of CMV infection in immunocompromised patients. CMV-associated enteric fistulae are an exceedingly rare complication, with only four previous cases described: a gastrocolic, an enterocutaneous, a rectovaginal and a colocutaneous fistula. Management of these patient demonstrates the importance of treating the precipitating viral infection before considering surgical intervention of the enterocolic fistula.